Smart study table / Nur Ikma Adila Edi Armiza ... [et al.]. - Edi Armiza, Nur Ikma Adila; Amirudin, Anastasia Tania; Abd Farouk, Nur Aqilah; Mohd Noordin, Nur A’isya Syaahirah; Zali, Siti Nur Aqilah (2024)
Brief description of the business and product concepts: StudySync Technologies, a pioneering force in educational technology, introduces the Smart Study Table. This innovative product combines state-of-the-art features, including an LED lighting system for optimized study environments, an embedded drawing tablet for interactive notetaking, a USB charging port for device convenience, a side small dustbin for efficient workspace organization, and a space-saving design catering to modern learning spaces. The Smart Study Table aims to revolutionize the study experience for students across various educational levels. The target market and projections: The Smart Study Table is designed to meet the diverse needs of students from K-12 to higher education. Market research indicates a growing demand for tech-integrated learning tools, and projections estimate a yearly market growth of 5%. The target market encompasses educational institutions, schools, and individual consumers who seek an advanced, multifunctional study solution. Initial sales forecasts project a steady increase, with an optimistic trajectory driven by the product’s versatile features.